2000
DOI: 10.1006/jfan.1999.3505
|View full text |Cite
|
Sign up to set email alerts
|

Heat Kernel Analysis and Cameron–Martin Subgroup for Infinite Dimensional Groups

Abstract: The heat kernel measure + t is constructed on GL(H), the group of invertible operators on a complex Hilbert space H. This measure is determined by an infinite dimensional Lie algebra g and a Hermitian inner product on it. The Cameron Martin subgroup G CM is defined and its properties are discussed. In particular, there is an isometry from the L 2 +t -closure of holomorphic polynomials into a space H t (G CM ) of functions holomorphic on G CM . This means that any element from this L 2 +t -closure of holomorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 9 publications
(4 reference statements)
2
40
0
Order By: Relevance
“…Gordina [10][11][12] considered the Taylor isomorphism in the context of Hilbert-Schmidt groups, while Cecil [2] considered the Taylor isomorphism for path groups over stratified Lie groups. The nilpotentcy of the Heisenberg like groups studied in this paper allow us to give a more complete description of the square integrable holomorphic function spaces than was possible in [10][11][12] for the Hilbert-Schmidt groups.…”
Section: Discussionmentioning
confidence: 99%
“…Gordina [10][11][12] considered the Taylor isomorphism in the context of Hilbert-Schmidt groups, while Cecil [2] considered the Taylor isomorphism for path groups over stratified Lie groups. The nilpotentcy of the Heisenberg like groups studied in this paper allow us to give a more complete description of the square integrable holomorphic function spaces than was possible in [10][11][12] for the Hilbert-Schmidt groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Taylor map isomorphism has also been proven for some infinite-dimensional groups: in [11] and [10] M. Gordina found a precise analog of this unitary isomorphism for the infinite-dimensional complex Hilbert-Schmidt orthogonal group, and in [12] she proved the analog for the group of invertible operators in a factor of type I I 1 . Also M. Cecil, in [3], has shown that a unitary Taylor isomorphism holds for path groups over stratified nilpotent Lie groups.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we continue to study the type of heat kernel analysis on infinitedimensional groups developed in [4], [5]. These papers dealt with so called HilbertSchmidt (infinite-dimensional) complex groups of operators on a Hilbert space.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference from the case of Hilbert-Schmidt groups studied in [4] and [5] is that the heat kernel measure lives in a space of unbounded operators, which makes the case of the II 1 -factor more complicated. Some of the new features are addressed in Section 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation